Relationship between UCS and Anisotropic Angle: A Case Study for Slate of Himalaya Region - Anand Gupta; Suman Panthee; Dr. Janani Selvam, (International Journal of Innovative Technology and Exploring Engineering (IJITEE), 2025)
The strength of rocks exhibits anisotropy, because of its mode of formation and its developing through different pressure and temperature environment. A rock can display anisotropy due to inhomogeneity, where sedimentary varying with the degree of the anisotropic plane. This "strength anisotropy" refers to the change in intact rock strength under uniaxial loading conditions based on the orientation of anisotropy, the strength and deformation behavior of rocks under load is critical for underground excavations, mining, and civil engineering projects, as it directly impacts the stability of such structures. This study examines the strength index, which is influenced by the anisotropic plane at different loading angles. The rock material, characterized by layers developed by platy minerals with sometime varying grain sizes, shows that an increase in foliation degree to loading angle directly impacts its strength. In slate, the strength index is influenced by the anisotropic plane and loading direction, which are also controlled by characters of mineral grains. This study seeks to enhance the existing understanding of this behavior by analyzing uniaxial compressive strength (UCS) performed on anisotropic low grade metamorphic rock